Adverse effect of anthropogenic activities on water quality of the Pekan River - Izzatulhanis, Rosli (2015)
A study on anthropogenic activities and water quality was carried out in the Pekan river, taking into account the location of the river which is at the centre of the Pekan city. The objectives of the study were to evaluate the water quality based on National Water Quality Standard (NWQS) and Water Quality Index (WQI) Malaysia of surface water quality in the Pekan river, and to identify the sources of pollution for sustainable management in the Pekan river. Three stations have been chosen to be tested its surface water condition. Station 1 was at the upper stream, and Station 3 on the downstream. Data of six in-situ parameters were collected; dissolved oxygen (DO), temperature, pH, electrical conductivity (EC), turbidity and salinity. The other parameters such as total suspended solids (TSS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammoniacal Nitrogen (AN), Sulphate, Phosphate and Heavy metals were test in laboratory. The results showed that BOD value was higher on Station 1 (11.02 mg/l) compared to other stations. The BOD value of the Pekan river was higher than the NWQS threshold level. The highest TSS value was at Station 3 (77.75 mg/l). Turbidity on Station 3 was higher (272.5 NTU). Overall, Pekan river was categorized as Class III based on WQI Malaysia, meaning the water cannot be used without proper treatment. The authorities should take action in controlling the condition of the river and establish the awareness of importance of river water among the community